Space Time Block Coding - Spatial Modulation for Multiple-Input Multiple- Output OFDM with Index Modulation System - Jyostnamayee Behera, Saradiya Kishore Parija, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, review to improve the channel estimation accuracy in OFDM system, channel state information is required for signal detection at receiver and its accuracy affects the overall performance of system and it is essential to improve the channel estimation for more reliable communications. A multiple-input multiple-output (MIMO) communication system combined with the orthogonal frequency division multiplexing (OFDM) modulation technique can achieve reliable high data rate transmission over broadband wireless channels. The performance of MIMO-OFDM is evaluated on the basis of Bit Error Rate (BER). The paper is aimed at analyzing the BER performance of the MIMO-OFDM system for Pilot Based Channel along with a simulation channel. We show that in the MIMO-OFDM system for Pilot Based Channel Estimation BER decreases, as the signal to noise ration increases. Simulation results show that the proposed estimator is able to reduce the BER effectively at high SNR’s and has a low computational complexity.